Risk factors for poor initial response to valproic acid therapy in children with epilepsy - Sari, Eva Devita; Anidar, Anidar; Amna, Eka Yunita; Andid, Rusdi; Yusuf, Sulaiman; Sovira, Nora (Indonesian Pediatric Society, 2025)
Background The initial response in the first three months of valproic acid therapy is a prognostic factor for predicting treatment success, and it is considered to be poor if seizures persist during the three months of valproic acid treatment. Several factors might influence the initial response to valproic acid therapy, including gender, age, family history of epilepsy, electroencephalogram (EEG), head circumference, type of seizure, cerebral palsy, and pre-therapy seizure frequency. Objective To determine the risk factors for poor early response to valproic acid therapy in children with epilepsy. Methods This retrospective cohort study was conducted in children newly diagnosed with epilepsy. Data were collected from medical records of patients who had been treated at the Pediatric Polyclinic of dr. Zainoel Abidin Hospital for one year. Results Of 90 subjects, most were male (58; 64.4%) and aged three years or older (79; 87.8%). Forty-five (50%) patients had a family history of epilepsy. More than a quarter of the subjects (35; 38.9%) showed initial poor responses to valproic acid therapy. Bivariate analysis revealed risk factors for poor initial response to valproic acid therapy were age ≥ 3 years, family history of epilepsy, normal EEG, normal head circumference, generalized seizure type, cerebral palsy, and pre-therapy seizure frequency. However, multivariate analysis revealed that risk factors for poor initial response to valproic acid therapy in children with epilepsy that retained significance were family history of epilepsy (RR 6.58; 95%CI 1.67 to 25.95; P=0,001), abnormal EEG (RR 5.27; 95%CI 1.16 to 23.87; P=0,000), focal seizures (RR 7.10; 95%CI 1.15 to 43.80; P=0,000), and cerebral palsy (RR 62.62; 95%CI 3.93 to 996.45; P=0,001). Conclusion The risk factors for poor initial response to valproic acid therapy in children with epilepsy are family history of epilepsy, abnormal EEG, focal seizures, and cerebral palsy.